FOXC1-induced Gli2 activation: A non-canonical pathway contributing to stemness and anti-Hedgehog resistance in basal-like breast cancer. (3rd May 2016) - Han, Bingchen; Qu, Ying; Yu-Rice, Yi; Johnson, Jeffrey; Cui, Xiaojiang
ABSTRACT: The Forkhead box C1 (FOXC1) transcriptional factor is a critical biomarker for basal-like breast cancer (BLBC). We recently reported that FOXC1 promotes cancer stem cell properties in BLBC by activating Smoothened (SMO)-independent Hedgehog (Hh) signaling, suggesting a FOXC1-mediated mechanism for BLBC cell function and anti-Hh therapy resistance.